International Efforts to Document Genocide Crimes in Iraq: The Role of the United Nations and Non-Governmental Organizations - Salem, Baneen (Journal of Legal Sciences, 2026)
Genocide constitutes one of the gravest international crimes threatening the existence of national, religious, and ethnic groups. Iraq witnessed horrific manifestations of this crime after 2014 through the atrocities committed by the Islamic State (ISIS) against minority communities, particularly the Yazidis. These violations underscored an urgent need for effective documentation mechanisms capable of preserving evidence, ensuring accountability, and preventing perpetrators from escaping justice. The United Nations has played a pivotal role in this regard through the international legal framework governing genocide prevention, alongside the efforts of its mission in Iraq (UNAMI) and the reports of the Office of the High Commissioner for Human Rights (OHCHR). A central milestone was Security Council Resolution 2379 (2017), which established the investigative team UNITAD, mandated to collect and preserve evidence in accordance with international standards of justice. In parallel, international non-governmental organizations such as Human Rights Watch and Amnesty International contributed significantly to uncovering facts and producing human rights reports. Likewise, Yazidi-focused organizations—such as Yazda and the Nadia Murad Initiative—played an essential role in documenting crimes and conveying survivors’ testimonies to the international community. Despite the challenges surrounding witness protection and coordination of evidentiary procedures, the convergence of efforts between the United Nations and non-governmental organizations forms a fundamental pillar for strengthening legal accountability and preventing the concealment of atrocities. This cooperation reaffirms the centrality of documentation as a vital tool for achieving transitional justice in Iraq.